2022
DOI: 10.3389/fnut.2022.964491
|View full text |Cite
|
Sign up to set email alerts
|

Is the binge-eating disorder a circadian disorder?

Abstract: and Golombek DA () Is the binge-eating disorder a circadian disorder? Front. Nutr. :. doi: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…For example, a systematic review by da Luz et al (2023) [87] found that people who binge eat exhibit poorer overall sleep quality compared to people who do not binge eat, and may have more daytime sleepiness, insomnia, and difficulty falling asleep. BED has even been proposed as a possible circadian disorder [88]. More studies of these associations might explain these relationships as well as the findings among pregnant women reviewed here [48,65].…”
Section: Discussionmentioning
confidence: 56%
“…For example, a systematic review by da Luz et al (2023) [87] found that people who binge eat exhibit poorer overall sleep quality compared to people who do not binge eat, and may have more daytime sleepiness, insomnia, and difficulty falling asleep. BED has even been proposed as a possible circadian disorder [88]. More studies of these associations might explain these relationships as well as the findings among pregnant women reviewed here [48,65].…”
Section: Discussionmentioning
confidence: 56%
“…Those who meet both NES core criteria, including evening hyperphagia and nocturnal ingestions, are at greater risk for experiencing more severe eating pathologies, including food addiction or binge eating [ 77 ]. In parallel, a close association has been suggested to link mood and chronotypes [ 78 , 79 , 80 ]. In particular, the eveningness chronotype is considered a risk factor for the development and remission of depressive symptoms, anxiety and major depressive disorder [ 78 , 81 , 82 , 83 ], independent of insomnia [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, a close association has been suggested to link mood and chronotypes [ 78 , 79 , 80 ]. In particular, the eveningness chronotype is considered a risk factor for the development and remission of depressive symptoms, anxiety and major depressive disorder [ 78 , 81 , 82 , 83 ], independent of insomnia [ 84 ]. Although the existence of altered, deficient cognitive–emotional processes have been implicated in this association, other factors associated with eveningness, including unhealthy lifestyle habits, a delayed dim light melatonin onset (DLMO) and the propensity of evening types to addiction may also charge this association [ 17 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advances in the understanding on how the circadian system may be involved in appetite/hunger and metabolic regulation, knowledge of its potential role in EDs lags behind ( 8 , 10 , 85 87 ). Virtually none of the assessments that have been performed to date can distinguish involvement of the circadian system vs. influences of the sleep/wake, rest/activity, dark/light, fasting/eating cycle, mood/impulse control rhythms, and/or social/work/school schedules in causing daily rhythms related to BE behavior.…”
Section: Potential Future Areas Of Researchmentioning
confidence: 99%